Successful treatment of two relapsed patients with t(11;19)(q23;p13) acute myeloid leukemia by CLAE chemotherapy sequential with allogeneic hematopoietic stem cell transplantation: Case reports - Tao, Shandong (Oncol Lett, 2021)
The prognosis of patients with relapsed/refractory acute myeloid leukemia (R/R AML) is poor, with a 3-year overall survival rate of 10%. Patients with translocation (t)(11;19)(q23;p13) have a higher risk of relapse and there is no optimal regimen for these patients. The present study treated two young patients with t(11;19)(q23;p13) AML, who relapsed after one or two cycles of consolidation, with a salvage treatment consisting of sequential cladribine, cytarabine and etoposide (CLAE) and allogeneic hematopoietic stem cell transplantation (allo-HSCT). Both neutrophil and platelet engraftments were achieved within 15 days, and no severe transplant-related complications and graft-versus-host diseases were observed. Following allo-HSCT, both patients achieved complete hematologic and cytogenetic remission. Decitabine was used for the prophylaxis of relapse. The two patients remained alive and disease-free for 100 days following allo-HSCT. The results presented here suggest that CLAE regimen sequential with allo-HSCT may be effective in treating patients with R/R AML, with t(11;19)(q23;p13). However, further studies and a larger sample size are required to validate the effectiveness of this treatment regimen.